AN EFFECTIVE STUDY OF GEOGRAPHICAL PATTERN AND INTENSITY OF DENGUE OUTBREAK AMONG MALES IN PUNJAB, PAKISTAN - Ahmad, Shahbaz; Asif, Muhammad; Majid, Muhammad; Iqbal, Manaza; Adeel, Muhammad (LIFE: International Journal of Health and Life-Sciences, 2018)
Dengue Fever is a hot issue under discussion around the world, specifically in tropical and sub-tropical countries. It is an epidemiological disease which covers the massive geographical area within no time from person to person. It is difficult to take over dengue fever with limited technical resources; administrative authorities should be equipped with technical resources and infrastructure. Geographical Information System (GIS) is well-developed technology to express all sort of information in thematically maps along with the reflection of hotspot areas. In this research paper, we used Arc View as GIS tool to exemplify Male Patient data of Dengue outbreak in Punjab 2011.In Punjab14500 male patients were registered in thirty-seven epidemiological weeks during this outbreak. This research analysis discovered significant results of geographical pattern and intensity of dengue fever among males belong to all districts of Punjab. These results can assist to Health departments and decision making authorities to make plans to avoid from future outbreak and emphasis on hotspot areas with preventive measures so that human and financial losses can control up to a minimum.